Marriage markets as explanation for why heavier people work more hours - Shoshana Grossbard; Sankar Mukhopadhyay (IZA Journal of Labor Economics, 2017)
Is BMI related to hours of work through marriage market mechanisms? We empirically explore this issue using data from the NLSY79 and NLSY97 and a number of estimation strategies (including OLS, IV, and sibling FE). Our IV estimates (with same-sex sibling's BMI as an instrument and a large set of controls including wage) suggest that a one-unit increase in BMI leads to an almost 2% increase in White married women's hours of work. However, BMI is not associated with hours of work of married men. We also find that a one-unit increase in BMI leads to a 1.4% increase in White single women's hours of work, suggesting that single women may expect future in-marriage transfers that vary by body weight. We show that the positive association between BMI and hours of work of White single women increases with self-assessed probability of future marriage and varies with expected cumulative spousal income. Comparisons between the association between BMI and hours of work for White and Black married women suggest a possible racial gap in intra-marriage transfers from husbands to wives.
Keywords: J22; I12; J12; 330; Obesity; Labor supply; Marriage; Marriage market; Gender; Race; Intra-household bargaining; Personal finances